Pocketbook of Clinical IR : A Concise Guide to Interventional Radiology - Altman, Ashley; Warhadpande, Shantanu; Lionberg, Alex; Cooper, Kyle J.; Becerra, Victor Nicholas; Chand, Rajat; Close, Orrie; Do, John; El-Ali, Alexander Maad; Fischman, Aaron M.; Gemmete, Joseph J.; Grierson, Patrick; et al. (Thieme, 2019)
Excel at clinical IR with insightful perspectives from both current residents and senior interventionalists! Interventional radiology training has evolved rapidly during the last decade, with recent recognition as a primary medical specialty by the American Board of Medical Specialties. The number of IR residency positions continues to increase each year with a greater number of trainees rotating through the IR elective. The bar is set high and expectations of trainees have increased. Written clearly, concisely, and at a trainee's level, Pocketbook of Clinical IR: A Concise Guide to Interventional Radiology by Shantanu Warhadpande, Alex Lionberg, and Kyle Cooper is the first IR pocketbook written specifically for medical students and junior residents to help them excel on their IR rotation. This book will help trainees to intelligently field IR consults, effectively round on patients, and develop an understanding of IR disease processes. Concise yet thorough, it provides a solid clinical foundation to underlying pathologies and procedures, and embodies the authors' philosophy that the IR education paradigm should be transformed into one in which the clinical care of patients is of equal importance to technical procedural training. Key Features Clinical background on hepatobiliary, oncologic, arterial, venous, genitourinary, and neurologic diseases frequently encountered in IR Insightful clinical algorithms provide guidance on how the IR procedure fits into the big picture Concise procedure boxes provide an overview of how the procedure is performed so the trainee can be an active participant in any IR procedure This practical white-coat companion is essential for all trainees involved with interventional radiology.
Keywords: Interventional radiology : Methods; Radiography, Interventional : methods